The Dynamics Of Students' Decisions In Palembang In Buying Local Clothes Amid The Dominance Of Imported Clothes, Reviewed From The Lifestyle Expected Value Perspective Price Perception - Hamid Halin; Nandan Limakrisna; Agus Setyo Pranowo (Penerbit dan Percetakan CV. Picmotiv, 2025)
This study aims to examine the influence of Lifestyle, Expected Value, and Price Perception on Purchasing Decisions. Data were collected from 366 student respondents in Palembang and analyzed using Structural Equation Modeling (SEM). The results showed that all three independent variables (Lifestyle, Expected Value, and Price Perception) had a positive influence on Purchasing Decisions. This finding confirms that in the context of purchasing local fashion products, price and value factors must be managed by strengthening brand image first.